Edukasi “Pelayanan Lansia Sehat Sejahtera” Implementasi UU No. 13 tahun 1998 Tentang Kesejahteraan Lanjut Usia - Imron Rosadi; Ade Burhan; Ai Astuti; Supiadin Supiadin (STAI Darul Qalam Tangerang, 2026)
The elderly, or older people, are individuals in the later stages of life, usually aged 60 years and above, and face various challenges that affect their physical, mental and social health. Health-wise, the elderly often suffer from chronic diseases such as hypertension, diabetes and heart disease that require long-term management. Declines in physical and cognitive function, including mobility, muscle strength, and thinking ability, are a natural part of the aging process. In addition, older adults are also prone to mental health issues, such as depression and anxiety, which are often caused by social isolation and loss of loved ones. Socially, many older adults feel lonely and isolated, especially after losing a spouse or friend,or if they do not have close family. Social support from family, friends and the community becomes crucial for their emotional well-being. From an environmental aspect, older people often live in housing that does not suit their needs, such as poor accessibility and unsafe neighborhoods. Difficulties in accessing the health, social and support services they need are also significant challenges. The care and support provided to older people, including regular health care and emotional and social support, iscrucial to improving their quality of life. However, financial limitations are often a barrier to getting the necessary care and meeting basic needs. In addition, existing policies and regulations sometimes do not adequately support the protection and care of older people. Understanding the challenges older people face and providing appropriate support is essential to ensure they can lead healthy and dignified lives in old age.